A National Survey of Glaucoma Specialists on the Preoperative (Trabeculectomy) Management of the Ocular Surface*. (1st November 2016) - Tailor, Rajen; Batra, Ruchika; Mohamed, Shabbir
Abstract: Background : Preserved anti-glaucoma drops cause ocular surface disease (OSD), which is increasingly being recognized as a likely cause of trabeculectomy failure. Aim : To determine the routine pre-trabeculectomy management of the ocular surface by glaucoma specialists. Methods : A questionnaire consisting of 11 questions was posted to 146 UK glaucoma specialists. Results : The first-time response rate was 43.8%. Regarding routine pre-operative management, 40.6% of specialists use preservative-free drops, 29.7% commence a drop holiday, and 53% advise lid hygiene. 42.1% prescribe lubricants, 50% prescribe topical steroids, 7.8% topical NSAIDs, and 34.4% systemic tetracyclines. 84.4% of specialists change their routine management if OSD is present. Pre-operative optimization of the ocular surface is viewed "necessary" by 48.4% and "beneficial" by 85.9%. Conclusion : A wide variation exists in the routine pre-operative management of the ocular surface. Research to determine the impact of different pre-operative interventions upon trabeculectomy outcomes is required.